Swine influenza surveillance in Italy uncovers regional and farm-based genetic clustering - Cavicchio, L.; Tassoni, L.; Pastori, A.; Carrino, M.; Gagliazzo, L.; Mion, M.; Ustulin, Martina; Vio, D.; Mantovani, C.; Ceglie, L.; Fusaro, A.; Beato, M. S. (Frontiers in Microbiology, 2025)
IntroductionSwine Influenza is a respiratory disease endemic in pigs with implications for animal and public health. Pigs, as mixing vessels for human, avian, and swine influenza strains, contribute to viral reassortment and emergence of new strains. Influenza viruses can circulate and spread unnoticed between pig farms for extended periods, heightening the risk of reassortment events. This study aimed to monitor swine Influenza virus (swIAV) genetic diversity in Northern Italy and understand its evolution in the study area.Material and methodsPassive surveillance, conducted from 2013 to 2022, involved 253 farms located in three regions, collecting over 3,000 samples that were tested for swIAV. Eighty-five samples underwent full genome sequencing, and phylogenetic analyses were conducted for each segment. In addition, cross-reactivity of viral strains was assessed using hemagglutination inhibition (HI) tests with hyperimmune swine sera.ResultsOf the tested farms, 37.9% were positive for swIAV on at least one sampling event. Twelve distinct genotypes were identified, including two novel genotypes in Italy, both detected in 2022. Phylogenetic analyses revealed the presence of strictly correlated viruses in farms sharing the same owner or geographical proximity and highlighted multiple introductions and reassortment events in some farms. Cross HI tests demonstrated minimal antigenic cross-reactivity between circulating swIAV strains.ConclusionThe study reveals a high genetic diversity in swIAV circulating in Northern Italy as a consequence of multiple virus introductions as well as new reassortment events with the identification of two new genotypes. The findings highlight the importance of sustained surveillance and genetic monitoring to track viral evolution and reassortment, which are pivotal for early detection of strains with pandemic potential.